CORPORATE SUSTAINABILITY PRACTICES OF THE EUROPEAN COMMISSION IN HIGHER EDUCATION - Özel, Meltem (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The world is facing two important problems such as climate change and environmental pollution. Unconscious consumption and industrialization also increase environmental pollution, making nature unable to renew itself. Everyone has a very important role in the regeneration of nature and the sustainability of resources. It will be possible to obtain a more sustainable and clean environment by separating wastes, by using resources more efficiently and economically. United Nations (UN) members met in 2015 and agreed on 17 Global Goals by 2030 for 3 key issues “eliminating extreme poverty, fighting inequality and injustice, fixing climate change.”. It is expected that these global goals for sustainable development will be realized for all people in all countries. It has become a necessity for institutions to place sustainable development and sustainability in their management policies for the future of the world. This study investigates how European Commission has adapted to the sustainability process and UN’s 17 Global Goals in Higher Education through examining its corporate sustainability strategies, and its relationship between its stakeholders. The European Green Deal Communication is the new growth strategy of European Union (UN) and recognises the key role of schools, training institutions and universities to engage with pupils, parents, and the wider community on the changes needed for a successful transition to become climate neutral by 2050. European Commission has internalized UN goals, has determined sustainability strategies in line with especially Goal 12 and Goal 13, has followed the European Green Deal missons and ECHE principles, and has implemented practices such as Erasmus Without Paper Network, EWP Dashboard and Green Travel. In this research, it has been revealed that the corporate sustainability strategies of the European Commission are in line with the objectives of the UN’s 17 Global Goals, not just on paper, and become widespread with various supported projects